Changing trends in the epidemiology of gastric cancer - Grad, Cosmin; Grad, Simona; Fărcaș, Radu A.; Popa, Stefan; Dumitrașcu, Dan L (Medicine and Pharmacy Reports, 2022)
Currently being the seventh most prevalent form of cancer worldwide, and the fifth most common cause of cancer-related death, based on GLOBOCAN 2020 data, gastric cancer is still an important public health problem, despite its dropping incidence. Regions around the world are still at high-risk, mostly in populations with a high prevalence of Helicobacter pylori infection or a carcinogenic favorable diet. Gastric cardia cancer incidence is on the rise in some areas. Great steps were made in the last decades in understanding the pathogenesis of gastric cancer and its risk factors. Host genetic polymorphisms play a quintessential role in disease outcome. Helicobacter pylori eradication and endoscopic surveillance are the most effective options to further decrease gastric cancer incidence. Surgery is required for a curative treatment in most cases. This review summarizes the latest worldwide epidemiological data of gastric cancer and aims to provide an accessible and credible source of evidence for physicians who assess risk factors for gastric cancer.